Man-land relationship based on the spatial coupling of population and residential land – A case study of Yuzhong County in Longzhong Loess Hilly Region, China. (May 2022) - Liu, Shichun; Ma, Libang; Yao, Yao; Cui, Xijuan
Abstract: Population and residential land use are the core elements of the rural man-land relationship system. The relationship between the rural population and residential land is of great significance to the study of the man-land relationship in rural regions. The Longzhong loess hilly region is one of the most vulnerable areas of social ecology and economy in China, with relatively poor natural conditions and economic development. In this paper, 268 administrative villages in Yuzhong County, Longzhong Loess Hilly Region, were used as evaluation units with spatial dislocation analysis methods to analyze the spatial distribution of population and residential land from a micro-spatial perspective. This shows the coupling relationship between population and residential land, and altitude gradient characteristics. Following conclusions are obtained: (1) Rural permanent residents, migrants, residential land area and idle homesteads show high spatial similarity. The areas with high density and geographic concentration are mainly concentrated in the central Chuanyuan area, and the areas with low ones are mainly distributed in the northern mountainous regions. (2) There is a highly coupled relationship between population and residential land in Yuzhong County. For the permanent population and residential land area, 89.18% of the administrative villages are in coordination, and 10.82% of the administrative villages are not coordinated. In terms of the proportion of the migrant population and the proportion of idle homesteads, 55.97% of the administrative villages are coordinated, and 44.03% of the administrative villages are not coordinated. (3) The altitude gradient effect on the "population-residential land" coupling relationship is significant. The permanent population and residential land area are mainly "H-H" type villages in low-altitude gradient areas, and "L-L" type villages in medium-high altitude gradient areas. The proportion of the outflow population and the proportion of idle homesteads of "L-L" type villages are the largest in low-altitude gradient areas, and that of "H-L" type villages are the largest in the middle and high-altitude gradient areas. This paper explored a new model of man-land relationship, and improved the theory of rural man-land relationship regional system. It is of great significance to promote the coordinated and sustainable development of loess hilly region and even the entire Loess Plateau in China. Highlights: Population and residential land use are the core elements of the rural man-land relationship system. The spatial coupling relationship between population and residential land was evaluated by spatial dislocation analysis. The spatial distribution and relationship between population and residential land under different altitude gradients were analyzed from the micro perspective. It is of great significance to study the relationship between man and land in rural areas.